Frequency of Causes of Mechanical Bowel Obstruction (Medical Forum Monthly, 2024)
Objective: To find out the frequency of different causes of mechanical bowel obstruction.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was carried out the Surgical B Unit of MTI, Lady Reading Hospital Peshawar from March 2015 to December 2015.Patients and Methods: All the patients presented with signs and symptoms of bowel obstruction were included in the study while those with non mechanical bowel obstruction like paralytic ileus and peritonitis were excluded from the study. Patient’s demographic features and all the data were recorded.Results: Total 50 patients were included in the study. The age range of the patient was 15-80 years with mean age was 42.98±17.60 years. Thirty seven 74% patients were male and 13 (26%) were female constituting male to female ratio of 2.84:1. Out of 50 patients operated for mechanical bowel obstruction, commonest cause of bowel obstruction was post operative adhesions which accounted for 17 (34%) followed by sigmoid volulus in 10 (20%) cases and intestinal tuberculosis in 8 (16%) patients.Conclusion: Adhesions and sigmoid volvulus were the common causes of intestinal obstruction. Although patients presenting with sub acute intestinal obstruction can be treated conservatively initially, should they develop signs and symptoms of gut ischemia, when conservative treatment fails or in most cases of acute intestinal obstruction immediate surgical exploration is still required.